1996
DOI: 10.1111/j.1365-2842.1996.tb00882.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cross‐linking agents on the water sorption and solubility characteristics of denture base resin

Abstract: Six different cross-linking agents were added to the monomer component of an autopolymerizing denture base resin, and their effects on the water sorption and solubility were investigated. The results of this study suggested that the chemical nature of the polymer versus that of the water molecule directly affected the water sorption of denture base resin. The addition of a cross-linking agent decreased the solubility with increasing concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
105
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 25 publications
5
105
0
6
Order By: Relevance
“…The Al 2 O 3 -added groups exhibited significantly lower water sorption values compared with those in group 4 (control) due to the insolubility of Al 2 O 3 nanoparticles in water. However, previous studies have indicated that the addition of nanoparticle fillers to improve the mechanical properties of PMMA increases the water sorption of acrylic resins (4,36,37). In particular, the increase in the nanoparticle filler ratio causes more water sorption because of more nanoparticle filler-matrix particle interface.…”
Section: Discussionmentioning
confidence: 99%
“…The Al 2 O 3 -added groups exhibited significantly lower water sorption values compared with those in group 4 (control) due to the insolubility of Al 2 O 3 nanoparticles in water. However, previous studies have indicated that the addition of nanoparticle fillers to improve the mechanical properties of PMMA increases the water sorption of acrylic resins (4,36,37). In particular, the increase in the nanoparticle filler ratio causes more water sorption because of more nanoparticle filler-matrix particle interface.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that water absorption is influenced by factors such as filler content 40,41) , presence of residual unpolymerized monomers, inclusion of air bubbles 42,43) , and the cross-linking degree of resin molecules 44,45) . In particular, incomplete polymerization might cause the physical properties of the resin material to deteriorate and microleakage to increase, thereby inducing color changes.…”
Section: Discussionmentioning
confidence: 99%
“…As the equilibrium water sorption is achieved in 24 h 5) , the control specimen in the present study seemed to reach water sorption saturation after 50 hours' water immersion. As the denture base resin was immersed in water, soluble constituents such as unreacted monomers, plasticizers, and initiators leached out 23) . The remaining microvoids formed were filled with water molecules through inward diffusion.…”
Section: Discussionmentioning
confidence: 99%